Dielectric properties, heating rate, and heating uniformity of various seasoning spices and their mixtures with radio frequency heating. (July 2018) - Ozturk, Samet; Kong, Fanbin; Singh, Rakesh K.; Kuzy, Jesse Daniel; Li, Changying; Trabelsi, Samir
Abstract: Low moisture foods, including seasoning spices, have been associated with a number of multi-state outbreaks of salmonellosis in the past decade. The long-term objective of this study was to develop an effective in-package pasteurization treatment for seasoning mixtures based on radio frequency (RF) heating. Seasoning spices obtained from grocery stores included red, white, and black pepper; cumin; curry powder; and garlic powder with moisture contents ranging from 3.1 to 12.3% (wet basis). The dielectric properties (DP) of the seasoning spices and their mixtures as influenced by frequency, moisture, temperature, mixing fraction and salt content were determined using a precision LCR meter and liquid test fixture at frequency ranging from 1 to 30 MHz. The RF heating rates of each spice and their mixtures were evaluated using a 27.12-MHz, 6-kW pilot scale RF system with 105 mm gap between electrodes. To evaluate the effect of mixing on heating uniformity, a sample (50 g) was placed into a polystyrene plastic cylindrical container and heated to 70 °C, and surface images were taken by an infrared camera. The results showed that the relationship among moisture content, temperature and DP of white pepper can be explained by a second-order model at 13.56 and 27.12 MHz. The DP and heating rates of spice mixtures ranged between the highest and lowest values of their respective individual spices. Increase in salt content resulted in a decrease in heating rate, which resulted a better heating uniformity with smaller uniformity index (UI). The RF heating rate of samples ranged from 2.97 to 23.61 (°C min −1 ). The highest heating rate in samples was in a correspondence to the worst heating uniformity, and highest average temperature on the sample surface. The most uniform heat distrubition on top surface was obtained for garlic powder as 0.012 (UI) at 70 °C. The information obtained from this study is important to develop an effective RF heating strategy for pathogen control in seasoning mixture. Highlights: Dielectric properties, RF heating rate and heating uniformity of seasoning spices and their mixture were determined. Effect of mixing of spices on RF heating rate and uniformity was evaluated. Effect of salt content (solid form) in spice mix on dielectric properties, heating rate and uniformity was studied.